Arbuscular mycorrhizal fungal communities associated with two dominant species differ in their responses to long‐term nitrogen addition in temperate grasslands. (13th March 2018) - Zheng, Zhi; Ma, Pengfei; Li, Juan; Ren, Lifei; Bai, Wenming; Tian, Qiuying; Sun, Wei; Zhang, Wen‐Hao
Abstract: Arbuscular mycorrhizal (AM) fungi are important components of grassland ecosystems and are sensitive to enhanced atmospheric nitrogen (N) deposition. Enhanced N deposition has been widely reported to reduce species richness and alter species composition across different types of grasslands world‐wide. Despite extensive studies on effects of N deposition on AM fungal communities of grasslands, few studies have specifically focused on effects of N deposition on AM fungi associated with dominant species in grasslands. We investigated long‐term (12‐year) effects of N addition (80 kg ha −1  year −1 ) on AM fungal community richness in roots and rhizosphere biomass of two dominant plant species (forb Artemisia frigida and grass Stipa krylovii ) in temperate steppes of northern China. We found that AM fungi associated with the two dominant plant species differed in their responses to N addition. Nitrogen addition led to a significant reduction in AM fungal richness colonized in roots, and biomass in the rhizosphere of A. frigida, while N addition had little impacts on AM fungi colonized in roots and rhizosphere of S. krylovii . Nitrogen addition significantly reduced AM fungal colonization in roots and AM fungal spore density in the rhizosphere soils of A. frigida . In contrast, N addition had no effect on AM fungal colonization in roots and spore density in the rhizosphere of S. krylovii . Nitrogen addition markedly suppressed photosynthetic rates in A. frigida due to excessive foliar accumulation of manganese. The N‐induced reduction in photosynthetic rates reduced allocation of C into roots in A. frigida, leading to a lower root/shoot ratio, and suppression of AM fungal community associated with A. frigida . The inhibition of AM fungi would render A. frigida less competitive in terms of acquisition of mineral nutrients in soils, thus contributing to its loss in the steppe community under conditions of elevated N deposition. These findings provide a mechanistic explanation for N‐evoked differential responses of AM fungal communities associated with A. frigida and S. krylovii by linking soil properties and host plants to AM fungal communities. A plain language summary is available for this article. Abstract : Plain Language Summary